THE CHRONOLOGY OF ANGLO‐SAXON STYLE POTTERY IN RADIOCARBON DATES: IMPROVING THE TYPO‐CHRONOLOGY. Issue 4 (17th September 2020) - Krol, Tessa N.; Dee, Michael; Nieuwhof, Annet
Summary: In the fourth and fifth centuries AD, the Anglo‐Saxon style was introduced in north‐western Europe. To what extent immigrants contributed to this process for each region is still debated. How and when the Anglo‐Saxon style spread is essential in this debate. Handmade pottery is the most common find category, but so far it can only be dated globally. An earlier and a later style have been postulated and the introduction of this pottery is seemingly not simultaneous in every region. Hitherto this could not be supported by the radiocarbon dates. The present study shows that, with the help of Bayesian modelling, it is possible to substantiate these patterns, which is of utmost importance for understanding migration patterns, contacts and exchange along the southern North Sea coastal regions during this period.